The Relationship Between Engineering and Young Women's Occupational Priorities - Davey, F. Heather (Canadian Journal of Counselling and Psychotherapy, 2007)
While women's participation rates in formerly male-dominated professions have increased markedly over the past three decades, engineering is a notable exception to the trend. This study investigated whether gender differences in occupational priorities might contribute to the paucity of women in engineering. Grade 12 students who had made occupational plans were asked the reasons for their choices. Results revealed that interests were the highest priority for male students, whereas altruistic values were more important to female students. Contrary to expectation, working conditions were not a factor. Implications for career counselling are discussed.